Levels and changes in cognitive, mental, and physical health as correlates of attitudes to aging in very old age - Sabatini, Serena; Numbers, Katya; Kochan, Nicole A.; Sachdev, Perminder S.; Brodaty, Henry (Frontiers in Psychiatry, 2025)
IntroductionStudies investigating the associations between change in health indicators and multidimensional measures of self-perceptions of aging in very old age are scarce. This study investigated whether levels of and 12-year changes in objective and subjective indicators of cognitive, mental, and physical health explain variance in the self-perceptions of aging of very old individuals at follow-up.MethodsParticipants were 174 individuals enrolled in the Australian Memory and Aging Study (mean age = 87.41; SD = 3.67; 60% women). As health indicators, we used global cognition, the Memory Assessment Clinic Questionnaire, the Goldberg Anxiety Scale, the Geriatric Depression Scale, number of diagnosed health conditions, and self-rated health. Self-perceptions of aging were assessed with the Laidlaw Attitudes to Aging Questionnaire, which comprises three subscales capturing perceived psychological growth, psychosocial loss, and positive physical change. Simple and multivariable linear regression models were estimated.ResultsCross-sectionally, in multivariable linear regression models, more anxiety symptoms were associated with higher psychosocial loss (R2 = 6%) and higher self-rated health (R2 = 14%) was associated with higher perceived positive physical change. Cognition was not significantly associated with attitudes to aging subscales. Longitudinally, less increase in depressive symptoms was associated with less perceived psychosocial loss (R2 = 5%) and with greater perceived positive physical change (R2 = 11%).ConclusionSelf-perceptions of aging in different domains are cross-sectionally associated with different health indicators. However, among cognitive, mental, and physical health indicators, changes in depressive symptoms are the most correlated with perceived psychosocial loss in very old age.